Final results of brentuximab vedotin combined with ifosfamide-carboplatin-etoposide in first refractory/relapsed Hodgkin lymphoma: a lymphoma study association phase I/II study. Issue 13 (10th November 2022) - Stamatoullas, Aspasia; Ghesquières, Hervé; Feugier, Pierre; André, Marc; Le Bras, Fabien; Gac, Anne-Claire; Borel, Cécile; Gastinne, Thomas; Quittet, Philippe; Morschhauser, Franck; Ribrag, Vincent; Guidez, Stephanie; et al.
Abstract: This phase I/II study assessed the combination of brentuximab vedotin (BV) with ifosfamide-carboplatin-etoposide (ICE) as a second-line therapy in refractory/relapsed (R/R) classical Hodgkin lymphoma (cHL) patients. Phase I study was designed to determine the maximum tolerated dose (MTD) of BV (10 patients) and phase II evaluated the rate of complete metabolic response (CMR) after 2 cycles of BV-ICE (42 patients). There were no dose-limiting toxicities (DLT) during phase I recommending BV 1.8 mg/kg for phase II. Twenty-six patients (61.9%) achieved CMR after 2 cycles of BV-ICE and 37 patients (88%) were transplanted. With a median follow-up of 38 months, the 3-year progression free survival (PFS) and overall survival (OS) rate were 64.3% and 100%, respectively. Hematological toxicities (81%) and infections (21%) were the most frequent adverse event encountered BV-ICE regimen is feasible with manageable toxicities and could be an alternative to other salvage treatments. Trial Registration : ClinicalTrials.gov identifier: NCT02686346